Calidad de vida en pacientes con hemodiálisis - Corral Ramírez, Erick Andrés (2025)
Quality of life refers to the general perception of an individual's well-being, taking into account physical, emotional, social, and functional health. In patients with chronic kidney disease (CKD), this perception is altered due to the progressive deterioration of kidney function, which affects not only physical health but also psychological and social aspects. The condition of patients undergoing hemodialysis impacts not only their physical health but also their emotional and social well-being. The objective of the study was to analyze the quality of life in patients undergoing hemodialysis. To this end, documentary research with a descriptive approach was conducted, based on the review of 96 articles. The findings revealed that the impact of chronic kidney disease (CKD) and its treatment is multifactorial. Symptoms such as cramps, pain, fatigue, and weakness significantly reduce the ability to perform daily activities. In addition, psychosocial factors may negatively influence overall well-being, affecting patients' quality of life due to the limitations imposed by the disease on daily routines, as well as the uncertainty it generates regarding the future and ongoing treatment. The nursing role transcends physical, emotional, and psychological care, integrating activities based on Callista Roy's theory, such as establishing light physical activity routines, nutrition education, facilitating support groups, and promoting self-care and self-acceptance. Thereby contributing to the mitigation of the suffering associated with the disease and its treatment.